Employer-Provided Severance Pay: The Emergence of Job Displacement Insurance, 1930–1954 - Donald O. Parsons (Institute of Labor Economics (IZA), 2017)
Employer-provided severance pay plans became common during the Great Depression, a reaction to (i) large-scale layoffs of long-service workers, and (ii) the growing formalism of the employment relationship. Reasonably consistent series are constructed for severance plan coverage and structure by broad occupational group (office or factory workers) over the next two decades based on an ambitious series of surveys conducted by the National Industrial Conference Board. By 1953/54, approximately one-third of surveyed companies reported having a formal severance plan for nonexempt salary workers and one-sixth for hourly workers. Over much of the period, modal long-service plans offered benefits of a week's pay for each year of service, although many firms, especially those outside the manufacturing sector, offered flat-rate "notice" payments of only a week or two. Surprisingly, coverage levels were only modest higher in 1954 than in the late 1930s. The stability of plan coverage and design in the face of large changes in economic conditions and labor relations remains a puzzle.
Keywords: J65; J32; J33; 330; severance pay; wage insurance; unemployment insurance; job displacement insurance; advance notice; layoff; Great Depression